BRICS health and tuberculosis control collaborations during an era of global health (Medicine Anthropology Theory, 2015)
In this think piece, I examine the difference introduced by BRICS (Brazil, Russia, India, China, and South Africa) health collaborations in an era of global health. Using tuberculosis control as a grounding example, I show that BRICS collaborations prioritize: state-led solutions, particularly through policies aimed at expanding universal health coverage; scientific and programmatic innovation; experience and technology sharing; clear benchmarks for progress, based on current best practices of control; and flexibility. Unlike international health, BRICS health collaborations are not primarily concerned with preventing the importation of infectious disease across national borders. Nor are they based on global health’s concerns about global biosecurity or humanitarian biomedicine. Rather, BRICS collaborative health efforts fall within the nation-state paradigm, while also aspiring towards the global. They remain flexible in their operation, gesturing towards a neoliberal ethic. This flexibility allows BRICS to work within existing structures, while also establishing their own institutions from which to change traditional assistance relationships.